Penerapan Model Pembelajaran ARIAS (Assurance, Relevance, Interest, Assessment, Satisfaction) Terhadap Peningkatan Kemampuan Berbicara Bahasa Jepang SMA Negeri 110 Jakarta - Gabriella Inez Larasati; Nia Setiawati; Eva Jeniar Noverisa (Universitas Negeri Jakarta, 2025)
This study aims to determine implementation of the ARIAS (Assurance, Relevance, Interest, Assessment, Satisfaction) learning model to improve Japanese speaking skills of 11th grade students of SMA Negeri 110 Jakarta Academic Year 2023/2024. Students have difficulty in mastering Japanese speaking skills. The problems encountered by students are lack of confidence and motivation, participation in learning, and lack of vocabulary, grammar, and pronunciation in Japanese. ARIAS learning model is presented as one of the efforts to reduce the students’ problems. The research method used is pre-experimental one-group pretest-posttest design. The instruments used were oral test and questionnaire. The results showed that the Japanese speaking skill of the 11th grade students of SMA Negeri 110 Jakarta improved after using ARIAS learning model. From the questionnaire results, it can be concluded that the implementation of the ARIAS learning model is able to create more enjoyable and meaningful learning, increase students’ confidence, motivation, interest, and active involvement in the classroom.